2017
DOI: 10.1021/acs.jpcc.7b01312
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Water, Methanol, and Formic Acid on Fe2NiP, a Meteoritic Mineral Analogue

Abstract: The surface of an analogue to the meteoritic mineral schreibersite or (Fe,Ni) 3 P was investigated to provide insight into the interaction of the mineral surface with prebiotic molecules such as water, methanol, and formic acid. A protocol for creating synthetic metal-phosphide samples with a surface reflectivity suitable for reflection−absorption infrared spectroscopy (RAIRS) was developed and is outlined in this paper. Scanning electron microscopy coupled with energy dispersive spectroscopy revealed an avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 81 publications
3
23
0
Order By: Relevance
“…20 All these experiments clearly show the formation of oxygenated phosphorus compounds, in particular phosphites (HPO3 2-/H2PO3 -), more reactive and soluble than phosphates, and also the phosphorylation of organic compounds, including nucleosides. 18 An accurate study based on RAIRS (Reflection−Absorption InfraRed Spectroscopy) demonstrates that H2O molecules bind preferentially to P atoms on the schreibersite surface at low temperatures (120-140K), 21 this mechanism being also confirmed by isotopically enriched ( 18 O) water. 22 Recently, it has been proven that schreibersite is a good catalyst to also activate the reaction among carbohydrates to give more complex sugars (formose reaction network), accompanied by well-known oxygenated phosphorus species (phosphites and, in minor quantity, phosphates).…”
Section: Introductionmentioning
confidence: 99%
“…20 All these experiments clearly show the formation of oxygenated phosphorus compounds, in particular phosphites (HPO3 2-/H2PO3 -), more reactive and soluble than phosphates, and also the phosphorylation of organic compounds, including nucleosides. 18 An accurate study based on RAIRS (Reflection−Absorption InfraRed Spectroscopy) demonstrates that H2O molecules bind preferentially to P atoms on the schreibersite surface at low temperatures (120-140K), 21 this mechanism being also confirmed by isotopically enriched ( 18 O) water. 22 Recently, it has been proven that schreibersite is a good catalyst to also activate the reaction among carbohydrates to give more complex sugars (formose reaction network), accompanied by well-known oxygenated phosphorus species (phosphites and, in minor quantity, phosphates).…”
Section: Introductionmentioning
confidence: 99%
“…In laboratory investigations of the chemistry occurring within interstellar ices, however, ices are usually deposited onto flat surfaces used for transmission or reflection spectroscopy (e.g., gold, zinc selenide, magnesium fluoride, etc.). Although previous studies have acknowledged that adsorbent morphology may play an important role in the chemistry or spectroscopy of the adsorbate ice (Perets et al, 2007;Gull et al, 2015;Qasim et al, 2017;Wakelam et al, 2017;Pantaleone et al, 2021), there is a scarcity of studies that have considered this experimentally, and fewer still that have considered the chemical influence of the interaction of flat substrates with incident radiation. One study by Mason et al (2008) showed that the infrared spectrum of hexagonal crystalline water ice deposited over soot particles suspended in an ultrasonic trap differed somewhat to that of the same ice deposited onto flat fluoride substrates traditionally used in laboratory astrochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…20 All these experiments clearly show the formation of oxygenated phosphorous compounds, in particular phosphites (HPO3 2-/H2PO3 -), more reactive and soluble than phosphates, and also the phosphorylation of organic compounds, including nucleosides. 18 An accurate study based on RAIRS (Reflection−Absorption InfraRed Spectroscopy) demonstrates that H2O molecules bind preferentially P atoms on the schreibersite surface at low temperatures (120-140K), 21 this mechanism being also confirmed by isotopic water- 18 O. 22 Recently, it has been proven that schreibersite is a good catalyst to also activate the reaction among carbohydrates to give more complex sugars (formose reaction network), accompanied by well-known oxygenated phosphorous species (phosphites and, in minor quantity, phosphates).…”
Section: Introductionmentioning
confidence: 99%